COMMUNITY PARTICIPATION IN BAMBOO FOREST MANAGEMENT IN KITAKYUSHU CITY - Tamiya, Kana (Journal of Community Based Environmental Engineering and Management, 2021)
The fast growing bamboo causes problems in Kitakyushu as it is able to invade other plant areas. Bamboo forests that are growing too fast are often left without being properly cared for by landowners. This worsens the condition of the balance of the ecosystem in this bamboo forest area. In this study, an investigation was carried out on efforts to manage bamboo forests in Kitakyushu City, especially those involving the community. Efforts to manage bamboo forests are carried out by the government and the community in Kitakyushu City. The volunteers come from students and the general public. Activities carried out include providing experience for community members to cut bamboo trees, make musical instruments from bamboo and perform performances using these musical instruments. This activity instills awareness in the participants to better maintain the balance of the existence of this bamboo forest. The potential for the use of bamboo is actually very wide open, both as a musical instrument, souvenirs, cooking ingredients, construction materials, activated carbon and others. However, efforts to increase the benefit value of these products still have to be made to compete with other raw materials.